Recommendations arising from a workshop of experts to make the a.i.s. atm active drag assessment system more reliable and accurate - Mason, B.; Toussaint, H.; Kolmogorov, S.; Wilson, B.; Sinclair, P.; Schreven, S.; Sacilotto, G.; Hazrati, P.; Dominguez R. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
There is a real need in biomechanics to provide objective quantifiable parameters associated with free swimming to enhance the swimming performance of elite athletes. Active drag and propulsion profiles, with synchronised video footage of performance, are used at the Australian Institute of Sport (A.I.S.). The A.I.S. ATM assisted and resisted active drag system is used to achieve the above goal in real time. An active drag workshop was held at the A.I.S. to investigate the protocols and procedures that are used in the system and provide recommendations which if implemented would improve the system`s accuracy and efficiency. This paper addresses the suggestions provided by those world leaders of active drag research who were in attendance, in order to improve the capabilities of the A.I.S. ATM active drag system.